Tuberculosis with cavities? Rapid diagnosis of Rhodococcus equi pulmonary infection with cavities by acid-fast staining: A case report - Jiang, Yuhang; Li, Jian; Qin, Weichao; Gao, Yuan; Liao, Xin; Zeng, Yan (Frontiers in Public Health, 2022)
Rhodococcus equi is a conditionally pathogenic bacterium widely distributed in soil, water, and marine environments, which can cause respiratory infections, pleurisy, blood and even bone marrow infections in immunocompromised people, and particularly in patients with acquired immunodeficiency syndrome (AIDS). This case report describes a patient with initially suspicion of tuberculosis (TB) as an outpatient in a TB clinic. However, laboratory findings identified R. equi in his sputum sample based on a positive acid-fast stain, which was highly suggestive of a pulmonary infection caused by R. equi. The patient was subsequently admitted to the respiratory unit for treatment. Once the source of infection was identified, the patient was treated with a combination of antibiotics for 2 weeks and was discharged with a significant improvement in symptoms.